Evaluation of the risk factors for venous thromboembolism post splenectomy – A ten year retrospective cohort study in St James's hospital. (June 2021) - Abduljalil, Manal; Saunders, Jean; Doherty, Dearbhla; Dicks, Marthinus; Maher, Catherine; Mehigan, Brian; Flavin, Richard; Flynn, Catherine M.
Abstract: Background: Splenectomy is a surgical intervention for a variety of indications; benign and malignant. Complications of this procedure include Venous thromboembolism (VTE) and infection. The incidence of VTE post-surgery has been reported between 0.8%–3% depending on the type of surgery. A higher incidence of abdominal VTE was reported post splenectomy (6–11%). However, there is limited literature regarding the risk factors for post splenectomy VTE and the optimal strategy for thromboprophylaxis. Objective: The primary objective of the study was to evaluate the incidence of VTE post splenectomy and to identify the pre-operative, intra-operative and post-operative risk factors. The secondary objective was to assess the local compliance with post-splenectomy prophylactic antibiotics and vaccination protocols. Methods: We conducted a retrospective observational study. All patients who had a splenectomy in St James's Hospital between January 2007 and June 2017 were included and reviewed. Statistical analysis was carried out using SPSS statistical package. Results: 85 patients were involved in the study. The main indications for splenectomy were benign haematology, malignant haematology, solid tumours, traumatic and spontaneous rupture. 6/85 patients developed VTE (7.06%). High BMI ≥ 30 was associated with increased risk of VTE (p = 0.007), while the use of post-operative prophylactic anticoagulation was associated with reduced risk (p = 0.005). Other factors including age >50 years, female gender, presence of active malignancy and splenomegaly were associated with increased VTE risk with no statistical significance. All VTE's occurred in elective versus emergency splenectomy. Laparoscopic splenectomy was associated with higher risk of VTE than open splenectomy. 97% of patients were prescribed prophylactic antibiotics on discharge, but only 88% had received recommended vaccinations. Conclusion: Venous thromboembolism is common post splenectomy. Our data showed that BMI ≥30 was associated with a statistically significant increased risk of VTE, while the use of prophylactic anticoagulation was associated with reduced risk. Further prospective studies with larger samples are warranted and a splenectomy care plan may be helpful. Highlights: Venous thromboembolism is common post splenectomy procedure. High Body Mass Index can increase the risk of venous thromboembolism post splenectomy surgery. The use of extended prophylactic anticoagulation post splenectomy can reduce the venous thromboembolism complications. Many other factors can contribute to the venous thrombosis risk post splenectomy at variable extents.